Pelanggaran Etika dalam Proyek Pembangunan Dermaga di Pantai Mutiara, Jakarta Utara - Danang Dwi Sukmo Aji; Edison H Manurung (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
Infrastructure development in urban areas is often faced with various challenges, including ethical issues. The jetty construction project at Pantai Mutiara in Block SB Number 15 A, North Jakarta, is one prominent example in this regard. The jetty, designed to support maritime and tourism activities, has, since its inception, presented a range of issues related to ethical violations. These include manipulation of permits, misuse of funds, disregard for environmental impacts, and exploitation of labour. The ethical violations in this project not only harmed the environment and surrounding communities, but also undermined public trust in the government and related agencies. This case shows how important integrity, transparency and responsibility are in every stage of development. Through this study, we will take an in-depth look at the various aspects of the ethical violations that occurred in the jetty construction project at Pantai Mutiara, including the causes, impacts, and efforts that can be made to prevent similar occurrences in the future. By identifying and understanding the ethical breaches that occurred, it is hoped that valuable lessons can be learnt that can be applied to other development projects in Indonesia. Ultimately, the aim of this paper is to provide constructive recommendations to improve the planning and implementation process of infrastructure projects, so as to achieve a balance between development progress and the ethical principles that must be upheld.